2022
DOI: 10.3389/frai.2022.975029
|View full text |Cite
|
Sign up to set email alerts
|

Yes we care!-Certification for machine learning methods through the care label framework

Abstract: Machine learning applications have become ubiquitous. Their applications range from embedded control in production machines over process optimization in diverse areas (e.g., traffic, finance, sciences) to direct user interactions like advertising and recommendations. This has led to an increased effort of making machine learning trustworthy. Explainable and fair AI have already matured. They address the knowledgeable user and the application engineer. However, there are users that want to deploy a learned mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…B0, the smallest variant of this family, is nearly 0.6 times smaller and eight times more compute efficient than DenseNet121 [37], so this statement is clearly true, isn't it? We argue that such a statement is more nuanced and highly depends on the context, or in other words, execution environment [5]. As we will discuss in section 4.2, we found that inference with Densenet121 on a Raspberry Pi 4 CPU is nearly four times slower compared to EfficientNetB0.…”
Section: Consider the Following Three Examplesmentioning
confidence: 79%
See 1 more Smart Citation
“…B0, the smallest variant of this family, is nearly 0.6 times smaller and eight times more compute efficient than DenseNet121 [37], so this statement is clearly true, isn't it? We argue that such a statement is more nuanced and highly depends on the context, or in other words, execution environment [5]. As we will discuss in section 4.2, we found that inference with Densenet121 on a Raspberry Pi 4 CPU is nearly four times slower compared to EfficientNetB0.…”
Section: Consider the Following Three Examplesmentioning
confidence: 79%
“…In this context, it is important to remember that any model's performance is not only contingent upon its inherent algorithms. Instead, we find performance also being intricately affected by the environment that the model is executed in [5]. Any study thus needs to consider the question whether it really compares algorithms, implementations, or possibly both [6].…”
Section: Introductionmentioning
confidence: 86%
“…Nuanced assessments already exist in the field of environmental sustainability, for example in assessing the energy performance of household appliances, and there is already at least one attempt to produce a similar "Care Label" certification suite for Machine Learning, labeling not only energy consumption but also other features such as runtime, memory usage, expressivity, usability, and the reliability of the AI software [54,55]. This kind of assessment would be an excellent tool to audit the mentioned features separately and optimize AI systems to achieve a better balance of the performances in the different audit areas.…”
Section: Sustainability As An Audit Area For An Ethical Certification...mentioning
confidence: 99%